Deserción estudiantil en las carreras de ciencias de la salud en el Perú - Heredia Alarcón, Manuel (2015)
Background: The dropout rate in students of health sciences careers is scarcely investigated in our country. The university dropout in general is multifactorial in origin and implications, and includes individual, family, institutional and social factors. It causes huge economic losses to the country and to the region. Objectives: To determine the frequency of desertion during undergraduate training in medicine, nursing, obstetrics and dentistry in nine universities in Peru. Design: Retrospective observational cross-sectional study. Institution: Department of Management of Human Resources Development, Ministry of Health of Peru. Location: 4 universities of Lima and 5 universities of provinces. Methods: Record the number of students who withdrew during their training period in health sciences careers, and structured interviews to determine the conditioning factors. Main outcome measures: Number of deserters and conditioning factors. Results: The dropout rate was 10.20% in medicine, 11.11% in obstetrics, 9.91% in nursing, and 5.64% in dentistry. The most important factors influencing dropout were vocational and economic. Conclusions: The dropout rate in students of health sciences careers was 10% on average. The predominant reasons were vocational and economic. Universities emphasized monitoring of academic achievement, but they did not follow-up closely those who underperformed. Universities training students in the health field lack plans to assess for potential dropouts.